A clinical score to predict mortality in septic acute kidney injury patients requiring continuous renal replacement therapy: the HELENICC score. Issue 1 (December 2017) - da Hora Passos, Rogério; Ramos, João; Mendonça, Evandro; Miranda, Eva; Dutra, Fábio; Coelho, Maria; Pedroza, Andrea; Correia, Luis; Batista, Paulo; Macedo, Etienne; Dutra, Margarida
Abstract Background This study aimed to identify predictors of early (7-day) mortality in patients with septic acute kidney injury (AKI) who required continuous renal replacement therapy (CRRT). Methods Prospective cohort of 186 septic AKI patients undergoing CRRT at a tertiary hospital, from October 2005 to November 2010. Results After multivariate adjustment, five variables were associated to early mortality: norepinephrine utilization, liver failure, medical condition, lactate level, and pre-dialysis creatinine level. These variables were combined in a score, which demonstrated good discrimination, with a C-statistic of 0.82 (95% CI = 0.76–0.88), and good calibration (χ 2  = 4.3;p  = 0.83). SAPS 3, APACHE II and SOFA scores demonstrated poor performance in this population. Conclusions The HEpatic failure, LactatE, NorepInephrine, medical Condition, and Creatinine (HELENICC) score outperformed tested generic models. Future studies should further validate this score in different cohorts.